YouTuber icons: an analysis of the impact on buying behaviour of young consumers. (10th December 2019) - Misra, Pooja; Mukherjee, Ankita
Huge increase in the reach of internet in India has given rise to the new cult of celebrities known as 'social media influencers'. As people spend more hours on YouTube, their awareness has shifted to internet sponsored means of advertisement. Many brands are diversifying their marketing efforts into sponsoring such YouTubers/influencers. Brands need these influencers because consumers would trust a third person rather than the brand trying to directly advertise itself (Biaudet, 2017). This study aims to quantitatively analyse the influencer's major attributes that impact consumer's buying behaviour for the retail industry in NCR. The research showed that factors such as relatability, trendy, product details and interactivity of YouTube can influence consumer buying behaviour. This study investigates the influence that these factors have on consumer buying behaviour, in the Indian context through analysis which will provide empirical information for industry's reference in order to divide marketing efforts amongst different channels of communication.